In Vitro Evaluation of α-Amylase, α-Glucosidase Inhibition Activity and Protein Denaturation Inhibition of Polysaccharides from Leaves and Seeds of Zygophyllum album L. - Seddiki, Malika; Hadj, Mohammed Didi Ould El; Mohammed, Ahmed Messai; Boual, Zakaria; Belkhalfa, Hakim; Kemassi, Abdellah; Michaud, Philippe (Malaysian Applied Biology, 2025)
The present study investigates anti-hyperglycemic activity and protein denaturation inhibition of polysaccharide extracts from leaves (ZF) and seeds (ZG) of Zygophyllum album L (Zygophyllaceae), a wild plant harvested in the south-east of the Algerian Sahara. The global composition of the extracts was determined by spectrophotometric assays, and the monosaccharide composition was determined by TLC and HPLC-RID. The extraction yields were 0.53 ± 0.04% and 2.33 ± 0.52% for ZF and ZG, respectively. The leaf extract is rich in uronic acids (32.91 ± 0.23%) compared to the seed extract (5.98 ± 1.31%). The analysis of both extracts indicates that their composition of constituent monosaccharides is similar. ZF consists of 20.90% arabinose, 24.16% galactose, 22.88% xylose, 14.71% rhamnose, and 17.34% glucose, and ZG of 21.64% arabinose, 31.76% galactose, 16.95% xylose, 17.25% rhamnose, and 12.39% glucose. Their FT-IR spectra display the characteristic bands of polysaccharides. Seed extract shows a significant inhibitory effect against protein denaturation (IC50 of 0.93 ± 0.02 mg/mL & 22.75 ± 1.41 mg/mL for ZG & ZF, respectively). However, the leaf extract, with a low α-amylase inhibitory activity (IC50 of 90.16 ± 5.38 mg/mL) and a high α-glucosidase inhibitory power (IC50 of 5.44 ± 0.50 mg/mL), seems to be effective in reducing postprandial hyperglycemia.